Relationship of Vitamin D-Deficient Diet and Irisin, and Their Impact on Energy Homeostasis in Rats - Abulmeaty, Mahmoud Mustafa Ali; Almajwal, Ali M.; Alam, Iftikhar; Razak, Suhail; ElSadek, Mohamed F.; Aljuraiban, Ghadeer S.; Hussein, Khulood S.; Malash, Asmaa M. (Frontiers in Physiology, 2020)
Background and objective: Previous studies have identified the role of irisin and vitamin D in energy homeostasis. However, the effect of irisin and vitamin D on energy regulation has not been thoroughly investigated. Therefore, in this study, the effects of a vitamin D-deficient diet and irisin on total energy expenditure (TEE), food intake, and blood metabolites were investigated in rats. Methods: Sixteen healthy weaned male albino rats were randomly divided into two groups: a group fed a normal balanced growth diet (group A: n=8) and a group fed a normocalcemic diet that is vitamin D deficient with limited ultraviolet (UV) light exposure (group B, n=8). After six weeks, the volumes of respiratory gases were measured by open-circuit indirect calorimetry. Serum irisin, 25-OHVD3, calcium, insulin, and glucose levels were measured using ELISA. The respiratory quotient (RQ), energy expenditure, and Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) were calculated. Results: Rats with hypovitaminosis D were hypoirisinemic. Food intake, RQ (to the range of using endogenous fat), and glucose levels reduced significantly, while insulin levels increased. Bodyweight and TEE were non-significant changed. Additionally, irisin was strongly and positively correlated with body weight under normal conditions (r=0.905, p<0.01), and a moderate negative correlation in group B (r=-0.429, p<0.05). TEE and irisin showed no significant correlation. Conclusions: This study demonstrated that the early changes in energy homeostasis and irisin levels during states of hypovitaminosis D are affected by long-term consumption of a vitamin D-deficient diet with limited UV exposure.